Utilization of Sambiloto Extract Encapsulation with Foam Mat Drying Method in Drinking Water on Broiler Carcasses - Nilawati, Nilawati; Agustina, Agustina; Fati, Nelzi; Syukriani, Debby; Malvin, Toni (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This study aimed to evaluate the effect of Encapsulated Extract of Andrographis paniculata Leaves (EEOAPL), dried using the foam mat drying method and administered through drinking water, on the performance and carcass quality of broiler chickens. A total of 100 day-old broiler chicks were reared for five weeks in an open-house system using a Completely Randomized Design (CRD) with five treatments: A0 (commercial feed without extract), A1 (basal feed without extract), A2 (basal feed + 0.4% EEDS), A3 (basal feed + 0.8% EEDS), and A4 (basal feed + 1.2% EEDS). Each treatment was replicated four times with five birds per replicate. The results showed that final body weight ranged from 1503.25 g to 1896.50 g per bird, carcass percentage from 68.26% to 72.49%, abdominal fat from 1.435% to 1.553%, and performance index from 292.61 to 397.68. Statistical analysis revealed that EEDS supplementation had a highly significant effect (P<0.05) on final body weight, carcass percentage, and performance index, but no significant effect (P>0.05) on abdominal fat.